Senolytic therapy reduces inflammation in epithelial cells from COPD patients and in smoke-exposure mice - Baker, Jonathan R.; Daly, Leah; Hassibi, Shyreen; Kimura, Genki; Nishimoto, Yuki; Kizawa, Yasuo; Ito, Kazuhiro (Frontiers in Medicine, 2025)
IntroductionChronic obstructive pulmonary disease (COPD) is a disease of accelerated lung aging, with increased numbers of senescent cells found within the COPD Lung. Senescent cells may drive pathology by causing defective tissue repair and driving chronic inflammation via the release of inflammatory mediators known as the senescence-associated secretory phenotype (SASP). Senolytics are a new class of drugs that selectively remove senescent cells but have not previously been studied in COPD. We examined whether senescent cells are maintained during differentiation of COPD airway epithelial cells at the air–liquid interface and examined the role of the senolytic combination of dasatinib and quercetin on these cells and in a smoke-exposure mouse model.MethodsNon-smoker and COPD bronchial epithelial cells were differentiated at air–liquid interface (ALI). Senescence markers (p16INKA and p21WAF1) were determined using Western blotting and SASP factors via Olink proteomics and Meso Scale Diagnostics (MSD). Cells and 11 days cigarette smoke (CS)-exposed mice were treated with the senolytic cocktail of dasatinib and quercetin (D + Q).ResultsIncreased senescence markers were maintained in COPD ALI epithelium when differentiated at air–liquid interface, and treatment with D + Q reduced senescence markers, proteases, and Th2 cytokines. Therapeutic oral treatment of D + Q to CS-exposed mice reduced senescence burden while reducing inflammatory cell infiltrates and mouse CXCL1.ConclusionCOPD subjects show increased airway epithelial senescence, and these cells can be cleared therapeutically using the senolytic cocktail of D + Q, reducing broad-spectrum pulmonary inflammation in vitro and in vivo.